Intensitas Moral, Sifat Machiavellian dan Keseriusan Pelanggaran terhadap Intensi Whistleblowing Pegawai Pajak - Merliyana Merliyana; Asep Saefurahman; Enung Siti Saodah (Jurnal Manajemen, 2022)
This study aims to analyze the effect of moral intensity, machiavellian nature and seriousness of violations on whistleblowing intention. The population in this study were all tax employees in East Jakarta. The sample in this study were 88 respondents. This study uses an associative research strategy. In this research, the research method used is quantitative. The data used in this study are primary data in the form of questionnaires and the data processing method used in this study is multiple linear regression analysis. The results of this study indicate that moral intensity, machiavellian nature and seriousness of violations have a significant effect on whistleblowing intention.